Food Choice Experiments Indicate Selective Fungivorous Predation in Fisculla terrestris (Thecofilosea, Cercozoa). (25th August 2018) - Dumack, Kenneth; Pundt, Julia; Bonkowski, Michael
Abstract: Thecofilosea is a class in Cercozoa comprising mainly freshwater inhabiting algivores. Since direct observation of amoeboid protists in soil is not possible, the prey spectra of their terrestrial relatives remain obscure. To test for grazing selectivity and the preferred prey of terrestrial thecofiloseans, we conducted a food choice experiment including yeasts and algae as prey. When being offered all food sources at once, the yeast cells were strongly reduced, whereas the abundance of the algae only slightly decreased. Since Fisculla terrestris thrives with fungal prey, it must be considered as a predator of eukaryotes with high preference for fungal cells.